At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's solve the system of simultaneous equations step by step.
The given equations are:
1. [tex]\(y = x + 4\)[/tex]
2. [tex]\(x^2 + y^2 = 40\)[/tex]
Step 1: Substitute the expression for [tex]\(y\)[/tex] from equation 1 into equation 2.
[tex]\[ y = x + 4 \][/tex]
Substituting [tex]\(y\)[/tex] into [tex]\(x^2 + y^2 = 40\)[/tex]:
[tex]\[ x^2 + (x + 4)^2 = 40 \][/tex]
Step 2: Expand the squared term in the equation.
[tex]\[ x^2 + (x^2 + 8x + 16) = 40 \][/tex]
[tex]\[ x^2 + x^2 + 8x + 16 = 40 \][/tex]
[tex]\[ 2x^2 + 8x + 16 = 40 \][/tex]
Step 3: Simplify and solve the resulting quadratic equation.
[tex]\[ 2x^2 + 8x + 16 - 40 = 0 \][/tex]
[tex]\[ 2x^2 + 8x - 24 = 0 \][/tex]
[tex]\[ x^2 + 4x - 12 = 0 \][/tex]
Step 4: Factor the quadratic equation.
[tex]\[ (x + 6)(x - 2) = 0 \][/tex]
Step 5: Solve for [tex]\(x\)[/tex].
The solutions for [tex]\(x\)[/tex] are:
[tex]\[ x + 6 = 0 \quad \Rightarrow \quad x = -6 \][/tex]
[tex]\[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \][/tex]
Step 6: Use the values of [tex]\(x\)[/tex] to find the corresponding values of [tex]\(y\)[/tex] from equation 1.
For [tex]\(x = -6\)[/tex]:
[tex]\[ y = -6 + 4 = -2 \][/tex]
For [tex]\(x = 2\)[/tex]:
[tex]\[ y = 2 + 4 = 6 \][/tex]
Step 7: Write the solutions as ordered pairs [tex]\((x, y)\)[/tex].
The solutions to the system of equations are:
[tex]\[ (-6, -2) \][/tex]
[tex]\[ (2, 6) \][/tex]
Therefore, the solutions to the given system of equations are:
[tex]\[ \boxed{(-6, -2), (2, 6)} \][/tex]
The given equations are:
1. [tex]\(y = x + 4\)[/tex]
2. [tex]\(x^2 + y^2 = 40\)[/tex]
Step 1: Substitute the expression for [tex]\(y\)[/tex] from equation 1 into equation 2.
[tex]\[ y = x + 4 \][/tex]
Substituting [tex]\(y\)[/tex] into [tex]\(x^2 + y^2 = 40\)[/tex]:
[tex]\[ x^2 + (x + 4)^2 = 40 \][/tex]
Step 2: Expand the squared term in the equation.
[tex]\[ x^2 + (x^2 + 8x + 16) = 40 \][/tex]
[tex]\[ x^2 + x^2 + 8x + 16 = 40 \][/tex]
[tex]\[ 2x^2 + 8x + 16 = 40 \][/tex]
Step 3: Simplify and solve the resulting quadratic equation.
[tex]\[ 2x^2 + 8x + 16 - 40 = 0 \][/tex]
[tex]\[ 2x^2 + 8x - 24 = 0 \][/tex]
[tex]\[ x^2 + 4x - 12 = 0 \][/tex]
Step 4: Factor the quadratic equation.
[tex]\[ (x + 6)(x - 2) = 0 \][/tex]
Step 5: Solve for [tex]\(x\)[/tex].
The solutions for [tex]\(x\)[/tex] are:
[tex]\[ x + 6 = 0 \quad \Rightarrow \quad x = -6 \][/tex]
[tex]\[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \][/tex]
Step 6: Use the values of [tex]\(x\)[/tex] to find the corresponding values of [tex]\(y\)[/tex] from equation 1.
For [tex]\(x = -6\)[/tex]:
[tex]\[ y = -6 + 4 = -2 \][/tex]
For [tex]\(x = 2\)[/tex]:
[tex]\[ y = 2 + 4 = 6 \][/tex]
Step 7: Write the solutions as ordered pairs [tex]\((x, y)\)[/tex].
The solutions to the system of equations are:
[tex]\[ (-6, -2) \][/tex]
[tex]\[ (2, 6) \][/tex]
Therefore, the solutions to the given system of equations are:
[tex]\[ \boxed{(-6, -2), (2, 6)} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.